Costs, quality of life and cost-effectiveness of arthroscopic and open repair for rotator cuff tears: an economic evaluation alongside the UKUFF trial - Murphy, J; Gray, A; Carr, A; Cooper, C; Cooper, D; Ramsay, C (British Editorial Society of Bone and Joint Surgery, 2016)
Aims A trial-based comparison of the use of resources, costs and quality of life outcomes of arthroscopic and open surgical management for rotator cuff tears in the United Kingdom NHS was performed using data from the United Kingdom Rotator Cuff Study (UKUFF) randomised controlled trial. Patients and Methods Using data from 273 patients, healthcare-related use of resources, costs and quality-adjusted life years (QALYs) were estimated at 12 months and 24 months after surgery on an intention-to-treat basis with adjustment for covariates. Uncertainty about the incremental cost-effectiveness ratio for arthroscopic versus open management at 24 months of follow-up was incorporated using bootstrapping. Multiple imputation methods were used to deal with missing data. Results There were no significant differences between the arthroscopic and open groups in terms of total mean use and cost of resources or QALYs at any time post-operatively. Open management dominated arthroscopic management in 59.8% of bootstrapped cost and effect differences. The probability that arthroscopic management was cost-effective compared with open management at a willingness-to-pay threshold of £20 000 per QALY gained was 20.9%. Conclusion There was no significant overall difference in the use or cost of resources or quality of life between arthroscopic and open management in the trial. There was uncertainty about which strategy was most cost-effective.